The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3164/jcbn.21-123
|View full text |Cite
|
Sign up to set email alerts
|

Successful endoscopic hemostasis compared to transarterial embolization in patients with colonic diverticular bleeding

Abstract: Transarterial embolization (TAE) is performed in patients with colonic diverticular bleeding after difficult endoscopic hemostasis or rebleeding. A total of 375 patients with hematochezia at our hospital from 1 April 2016 to 31 March 2020 were retrospectively analysed. Firstly, we compared the group in which hemostasis was achieved by endoscopy alone with the group that eventually underwent TAE. Secondly, we compared the group in which hemostasis was achieved by endoscopy alone, with the group switched to TAE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
(31 reference statements)
0
5
2
Order By: Relevance
“…[30] In the present study, over 50% of the patients with upper GI bleeding who underwent hemodialysis were prescribed proton pump inhibitors or H2-receptor blockers as a prophylactic measure. The reason why the complication rate of upper GI bleeding in hemodialysis patients in the present study was high compared to the previous study [7,21,[28][29][30] is unknown, and warrants further prospective studies with an increased number of patients. Notably, patients with upper GI bleeding often have several comorbidities, such as ischemic heart disease, cerebrovascular disease, and infectious diseases.…”
Section: Upper Gi Bleedingcontrasting
confidence: 61%
See 3 more Smart Citations
“…[30] In the present study, over 50% of the patients with upper GI bleeding who underwent hemodialysis were prescribed proton pump inhibitors or H2-receptor blockers as a prophylactic measure. The reason why the complication rate of upper GI bleeding in hemodialysis patients in the present study was high compared to the previous study [7,21,[28][29][30] is unknown, and warrants further prospective studies with an increased number of patients. Notably, patients with upper GI bleeding often have several comorbidities, such as ischemic heart disease, cerebrovascular disease, and infectious diseases.…”
Section: Upper Gi Bleedingcontrasting
confidence: 61%
“…Although the complication rate of GI bleeding was relatively high during hemodialysis, successful endoscopic hemostasis was achieved in all patients in the present study. Although several previous studies have suggested that performing hemostasis in hemodialysis patients is challenging, [6,7,9,13,19,21] the present study found that hemodialysis had no detrimental effects on endoscopic hemostasis.…”
Section: Upper Gi Bleedingcontrasting
confidence: 45%
See 2 more Smart Citations
“…Ueda et al reported a higher shock index and extravasation on contrast-enhanced CT in patients who underwent TAE than in those who underwent endoscopic hemostasis; however, the outcomes and complications were not compared between the 2 groups. [42] Superselective arterial embolization has a high hemostasis rate (97%) and low intestinal ischemia and rebleeding rates (7% and 15%, respectively). [24] On the other hand, TAE has evaluated the efficacy and safety of TAE.…”
Section: Discussionmentioning
confidence: 99%